A COMPARISON OF TRANSLATION READABILITY BETWEEN GOOGLE TRANSLATE AND HUMAN TRANSLATOR IN THE MEDICAL BOOK ENTITLED ‘MEDICAL-SURGICAL NURSING’ - Ida Ayu Made Friska Setiawati; I. B. Putra Yadnya; I Nyoman Aryawibawa (Lingua Scientia, 2020)
This study aims to analyze the readability of translation outputs by Google Translate and huThis study aims to analyze the readability of translation outputs by Google Translate and human translator. This study was categorized as a descriptive qualitative research that the scale of readability level was used to analyze the data. The source text was the English text from the book ‘Medical-Surgical Nursing’, while the target text was the translation outputs produced by Google Translate. The Indonesian version of this book entitled ‘Keperawatan Medikal Bedah’ was used as the output of the target language which was produced by human translators. A questionnaire in the form of a Google Form was distributed to nine respondents to determine the readability level of each translation.  The result showed that the percentage of readability level produced by Google were 52% highly readable, 29.6% readable, 16% somewhat difficult, and 2.4% very difficult. Meanwhile, the readability level of the human translation was 55.1% highly readable, 31.2% readable, 12.6% somewhat difficult, and 1.1% very difficult. The results indicated that there is a slight difference of 4% in the result of the readability level produced by Google Translate and human translators. The result of the translations prove that the result of Google’s translation is now more natural, almost as natural as human translation, and makes it easier to understand. However, the results of the translation produced by Google Translate still require an editing process by human translators to produce a more contextual translation.man translator. This study was categorized as a descriptive qualitative research that the scale of readability level was used to analyze the data. The source text was the English text from the book ‘Medical-Surgical Nursing’, while the target text was the translation outputs produced by Google Translate. The Indonesian version of this book entitled ‘Keperawatan Medikal Bedah’ was used as the output of the target language which was produced by a human translator. A questionnaire in the form of a Google Form was distributed to the nine respondents to determine the readability level of each translation.  The result showed that the percentage of readability level produced by Google were 52% highly readable, 29.6% readable, 16% somewhat difficult, and 2.4% very difficult. Meanwhile, the readability level of the human translation was 55.1% highly readable, 31.2% readable, 12.6% somewhat difficult, and 1.1% very difficult. The results indicated that there is a slight difference of 4% in the result of the readability level produced by Google Translate and human translator. This proves that the result of Google’s translation is now more natural, almost as natural as human translation, and makes it easier to understand. However, the results of the translation produced by Google Translate still require an editing process by human translators to produce a more contextual translation.